Bersama Membangun Harapan: Kolaborasi dalam Proyek Sosial Panti Asuhan Yarhima 2 Bondowoso - Afila, Fransiska; N, Khavita Rahmania; D. R, Ernanda Mutiara; I, Putri Maulida; Amelyda; Puspito, Agung Nugroho (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This social project aims to help children at the Yarhima 2 Bondowoso Orphanage develop entrepreneurial skills through the social project of making bucket snack handicrafts. This activity is designed as a first step to provide them with practical skills that can support their future economic independence. The background of this project is based on the fact that labor conditions in Indonesia still face various challenges. Increasingly fierce job competition, a mismatch between the skills of job seekers and the needs of the labor market, and the limited availability of formal employment are the main factors that make it difficult for many individuals. Snack buckets have gained traction since early 2010, both as a unique gift and a promising business opportunity. Therefore, through the social project of making bucket snacks, it is hoped that the children of the Yarhima 2 Bondowoso Orphanage will gain the skills to make handicraft products in the form of bucket snacks and develop the motivation for them to be able to create business opportunities independently as an alternative solution to limited access to formal employment in the future.